A Novel Rhabdovirus Isolated from the Straw-Colored Fruit Bat Eidolon helvum, with Signs of Antibodies in Swine and Humans - Binger, Tabea; Annan, Augustina; Drexler, Jan Felix; Müller, Marcel Alexander; Kallies, René; Adankwah, Ernest; Wollny, Robert; Kopp, Anne; Heidemann, Hanna; Dei, Dickson; Agya-Yao, Festus Courage; Junglen, Sandra; et al. (Journal of virology, 2015)
Bats have been implicated as reservoirs of emerging viruses. Bat species forming large social groups and roosting in proximity to human communities are of particular interest. In this study, we sampled a colony of ca. 350,000 individuals of the straw-colored fruit bat Eidolon helvum in Kumasi, the second largest city of Ghana. A novel rhabdovirus (Kumasi rhabdovirus [KRV]) was isolated in E. helvum cell cultures and passaged to Vero cells as well as interferon-competent human and primate cells (A549 and MA104). Genome composition was typical for a rhabdovirus. KRV was detected in 5.1% of 487 animals, showing association with the spleen but not the brain. Antibody prevalence was 11.5% by immunofluorescence and 6.4% by plaque reduction virus neutralization test (PRNT). Detection throughout 3 sampling years was pronounced in both annual wet seasons, of which only one overlaps the postparturition season. Juvenile bats showed increased viral prevalence. No evidence of infection was obtained in 1,240 female mosquitos (6 different genera) trapped in proximity to the colony to investigate potential vector association. Antibodies were found in 28.9% (5.4% by PRNT) of 107 swine sera but not in similarly large collections of sheep, goat, or cattle sera. The antibody detection rate in human subjects with occupational exposure to the bat colony was 11% (5/45 persons), which was significantly higher than in unexposed adults (0.8% [1/118]; chi square, P < 0.001). KRV is a novel bat-associated rhabdovirus potentially transmitted to humans and swine. Disease associations should be investigated. IMPORTANCE Bats are thought to carry a huge number of as-yet-undiscovered viruses that may pose epidemic threats to humans and livestock. Here we describe a novel dimarhabdovirus which we isolated from a large colony of the straw-colored fruit bat Eidolon helvum in Ghana. As these animals are exposed to humans and several livestock species, we looked for antibodies indicating infection in humans, cattle, swine, sheep, and goats. Signs of infection were found in swine and humans, with increased antibody findings in humans who are occupationally exposed to the bat colony. Our data suggest that it is worthwhile to look for diseases caused by the novel virus in humans and livestock.